VACCINATION PROGRAM AGAINST AVIAN METAPNEUMOVIRUS IN BROILERS - Ríos H., Rosa (2009)
A vaccination programme against Avian metapneumovirus (aMPV) in broilers was evaluated using a live virus vaccine against aMPV with the strain chicken 1062, title of 102.4 DICT50 sprayed at first day of age. The study conducted in two commercial farms of poultry growers, located in a region where the Swollen Head Syndrome (SHS) is prevalent. A flock of 185 593 1-day old broilers of both sexes, Cobb Vantress 500 line, were distributed in a vaccinated group against aMPV and a control group not vaccinated against aMPV. It was evaluated the presentation of SHS, intensity of respiratory signs, post mortem lesions, productive parameters, mortality, and serological response by indirect ELISA test. Only the vaccinated group had birds with SHS during the 3rd and 4th week of age, showing intense respiratory signs and severe post mortem lesions at respiratory tract level. The control group showed better performance than the vaccinated group (additional 106 and 75 g of body weight in males and females than controls, p<0.05), and 75 and 4 points less of conversion index in male and females than controls respectively. However, the control group had a higher accumulative mortality (0.64%) than the vaccinated group (0.42%), mainly due to congestive problems. The results suggested that in vaccination against aMPV in chicken broilers, males are more sensitive than females to the occurrence of SHS.